IMPACT OF THE COVID-19 PANDEMIC ON INCOME TOURISM SECTOR (Case Study of Gowa Regency) - Harda, Nurwahidayanti (ICOR: Journal of Regional Economics, 2023)
Tourism generates new jobs, production activities and economic progress (GRDP), private sector growth, and infrastructure development. In addition, tourism can increase state revenue through taxes, especially indirect taxes. However, the Covid-19 pandemic has an impact on tourism activities due to the lack of preparation, the actions taken in the emergency phase of the crisis are very inconsistent in formulating important policies to stakeholders. Forced recovery marketing communications have also not been optimal due to the outbreak that occurred over a long period of time. This is partly due to the lack of knowledge and lack of information at the national level. This research uses a quantitative approach with data sources in the form of secondary data in the form of time series taken from the Central Statistics Agency (BPS) of South Sulawesi Province, BPS of Gowa Regency, and data from the Tourism and Culture Office of South Sulawesi Province and Gowa Regency for the period 2012-2021.Multiple Regression Analysis, Classical Assumption Test, and Hypothesis Test were used in looking at the relationship between variables in the study. The results found that the Number of Visitors Variable (X1) has a positive and significant effect on tourism sector revenue with a regression coefficient value of 0.872870, the hotel room occupancy variable (X2) has a regression coefficient of -0.189532 which shows hotel room occupancy has a negative effect on tourism industry revenue. The variable length of stay of tourists (X3) shows a regression coefficient of 0.377479 which means that if the length of stay of tourists increases, the income from the tourism sector will also increase. The tourism expenditure variable (X4) has a positive and significant effect with a significance value, then the Covid-19 impact variable (X5) has no effect on tourism sector revenue. Keywords: Number of Tourist Visits, Hotel Room Occupancy, Tourist Length of Stay, Tourist Expenditure, Covid-19 Impact, Tourism Sector Revenue